2004
DOI: 10.1093/humrep/deh117
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free fetal DNA in maternal serum appears to originate from cyto- and syncytio-trophoblastic cells. Case report

Abstract: Circulating cell-free fetal DNA in maternal serum offers an early and non-invasive method for prenatal diagnosis, but the origin of this DNA is still unknown. We report the absence of the SRY gene in maternal serum of a pregnant woman despite male genitalia at ultrasound. The karyotype was 45,X after direct trophoblast analysis and 45,X/46,Xidic(Yp) after culture and in all fetal tissues studied. Due to the absence of the SRY sequence in maternal blood and in the cytotrophoblast, we presume that free fetal DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(121 citation statements)
references
References 5 publications
1
115
0
5
Order By: Relevance
“…Although the origin of cffDNA has not yet been completely understood, several studies support the hypothesis that cffDNA arises from trophoblasts in the placenta (Flori et al, 2004). Maternal plasma contains circulating cell-free DNA fragments originating from both the mother and the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Although the origin of cffDNA has not yet been completely understood, several studies support the hypothesis that cffDNA arises from trophoblasts in the placenta (Flori et al, 2004). Maternal plasma contains circulating cell-free DNA fragments originating from both the mother and the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] cffDNA present in the maternal blood is thought to originate from apoptosis of cytotrophoblast and syncytiotrophoblast cells. 4,5 During early embryogenesis, the blastocyst gives rise to both the trophoblast cells, which form the syncytiotrophoblast and cytotrophoblast cells of the placenta, and the inner cell mass, which forms the extraembryonic mesenchymal core of the chorionic villi, the amnion, and the embryo. 6,7 Direct chorionic villus (CV) preps reflect karyotypes derived from trophoblast cells, whereas cultured CV sampling (CVS) karyotypes reflect the mesenchymal core cells of the chorionic villi.…”
mentioning
confidence: 99%
“…Chim et al have reported that the SERPINB5 gene, coding for maspin, is hypomethylated in placental tissues and hypermethylated in maternal blood cells (11 ). Because the placenta is likely to be the major source of fetal DNA in maternal plasma (18,19 ), and as discussed above, the maternal hematopoietic cells are likely to be a major source of maternal DNA in maternal plasma, hypomethylated SERPINB5 sequences may serve as a marker for placental DNA in maternal plasma. The feasibility of this epigenetic approach for noninvasive prenatal diagnosis has been demonstrated by the good correlation between the concentrations of hypomethylated SERPINB5 sequences and SRY sequences from male fetuses in maternal plasma, and the clearance of SERPINB5 sequences from maternal plasma following delivery (11 ).…”
Section: Molecular Enrichment Strategies: Fetal Epigenetic Markers Anmentioning
confidence: 99%